PATHOMORPHOLOGICAL ESTIMATION OF THE EFFICACY OF ALLIUM CEPA FOR THE TREATMENT OF EXPERIMENTAL OPISTHORCHIASIS IN COMBINATION WITH RABBIT VIRAL HEMORRHAGIC DISEASE - A. A. Sidel'nikova; L. V. Nacheva (Российский паразитологический журнал, 2019)
Objective of research: To reveal the efficacy of Allium cepa used for traditional therapy of opisthorchiasis in combination with rabbit viral hemorrhagic disease by estimation of the degree of changes in internal organs. Materials and methods: Experiment was conducted on outbreed male rabbits with viral hemorrhagic disease in combination with opisthorchiasis. As traditional therapy, we used bulbs of white onion (Allium cepa L.). Each animal received daily 40-50 g of chopped onion. Pathologicoanatomic autopsy of dead animals that did not get treatment and animals that got treatment was carried out by the end of the second day after clinical manifestation of first symptoms (providing the macroscopic picture of all internal organs). Results and discussion: Macroscopic examination confirmed the presence of minimal residual changes in internal organs of experimental animals receiving traditional therapy. In opisthorchiasis combined with rabbit viral hemorrhagic disease, the use of onion as a medicine is reasonable due to decrease in structural changes of internal organs, primarily, liver. Basically the suggested traditional therapy is aimed at maintenance and repair of damaged organs of the host.